A New Cu2+-Selective Sensor Based On Schiff Base as an Ionophore in PVC Matrix (International Journal of Scientific Research in Science and Technology, 2025)
A new PVC based membrane sensor was constructed for determination of Cu2+ in various samples. The sensor exhibits a super-Nernstian slope of 29.1mV per decade over a wide concentration range (1×10-7 × 1x10-1 Mol L -1). It has a response time of about 15 s and can be used for at least 8 weeks without any divergence in potentials. The proposed sensor revealed very good selectivities for Cu2+ over a wide variety of other cations over a pH range 3–7. It was applied to the direct determination of copper in tap water samples and, as an indicator electrode, in potentiometric titrations of Cu2+ ion. The electrode was also successfully applied to the speciation of Copper in aqueous solutions.